Isolation, identification and evaluation of bacterial flora in plantation soils against phytophthora capsici of black pepper (piper nigrum L.) - Linda, Nirwana Caroline (University Malaysia Sarawak, UNIMAS., 2013)
The purpose of this study was to isolate, identify and evaluate the bacterial flora in the plantation soils against Phytophthora capsici of the black pepper (Piper nigrum L.). The screening of the antagonistic bacterial isolates was done through dual plate method against P.capsici. Three antagonistic bacteria (P1, P10 and P11) were successfully isolated. All of the three antagonistic bacteria were characterized based on its colony morphology, gram staining, production of diffusible and volatile antibiotics and the microscopic observation of the abnormalities toward hyphae morphology of P.capcisi. The molecular identification was conducted using 16S rDNA primers conducted and PCR products of 1500 bp in molecular weight of sizes were obtained and sequenced. The antagonistic bacteria isolate, P1 could not be identified. Meanwhile, isolate P10 was established as Burkhoderia unamae and isolate P11 as Enterobacter cloacae. The result of the study showed that B. unamae is the most effective antagonistic strain as compared to the other two antagonistic strains.